Assessment for learning : supervisory feedback practice in higher education - Talib, Rohaya (Serials Publications, 2016)
Assessment for learning is a term used to denote a continuous assessment of student’s progress with accompanying feedback to improve learning. So, this paper aims to investigate the assessment feedback (AFB) practices among supervisors in one of Higher Education (HE) institutions in Malaysia on three specific dimensions; Timeliness, Meaningfulness and Specificity. It also examined the significant mean difference of perceived Supervisory AFB practices in relation to postgraduate (PG) students’ gender, mode of study (MOS) and field of study (FOS) using crosssectional survey design. A total of 306 PG students who were currently pursuing their research studies have been selected using multistage cluster sampling technique. A self-developed instrument known as Supervisory Assessment Feedback Questionnaire (reliability index .92) which consisted of 38 items was used to collect the data. Overall result shown that Supervisory AFB practices were at the highest level for Meaningfulness (M=4.35, SD = .69), followed by Timeliness (M=4.35, SD =.69) and finally Specificity (M=3.85, SD= .53). The AFB forms practiced among supervisors resulted in verbal form (M=2.87, SD= .69) higher compared to written (M=2.77, SD= .71) meanwhile the PG students’ preferences were in both. Besides, the supervisory AFB practiced seems to be significantly differed on gender factor. In summary, these results revealed some insight to be considered in order to establish an effective Supervisory AFB practice in Malaysian HE.